PANDANGAN PEMILIH PEMULA PADA ORGANISASI PIMPINAN CABANG IKATAN PELAJAR MUHAMMADIYAH KECAMATAN NGORO TERHADAP PRAKTIK MONEY POLITIC DALAM PEMILU 2024 - Masyitha, Izza; Purba, Iman Pasu Marganda Hadiarto (Kajian Moral dan Kewarganegaraan, 2024)
This study aims to determine to describe the views of the beginner voters in Pimpinan cabang Ikatan pelajar Muhammadiyah of Ngoro on the presence of political money practices in the 2024 general election. The data collection techniques used are observations, interviews, and documentation. This research uses a type of descriptive qualitative research. This study involves a beginner voter in the organization Pimpinan cabang Ikatan pelajar Muhammadiyah of Ngoro district with a total of 13 people. The results of the study show that beginner voters have different views on the existence of money political practices that occurred in the 2024 elections, there are beginners voters considering that money political practice as a logical and permissible thing, voters view that money politics practices carried out by a candidate politician, indicate the seriousness of candidate politicians in nominating themselves. Furthermore, the provision of money by candidate politicians is used as a form of maximization of utilities such as satisfaction of needs and so on. Other novice voters view money-politics as an election violation, changing one's political choices in an unfair way, by giving a bribe or bribes.